Learning and organizational change: Attitudes towards organizational change and learning strategies at work relationships - Neiva, Elaine Rabelo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2012)
The objective of the present study was to relate the attitudes towards organizational change and the learning strategies at work in three distinct Brazilian organizations. The respondents were 299 employees of the three organizations: two organizations from the public-sector and a private company. A questionnaire about strategies of learning at work and the scale of attitudes towards the organizational change were applied to participants. The results had been analyzed by descriptive and inferential statistics such as means and standard deviation and analyses of multiple regressions. The descriptive results were similar to previous studies. The relations between attitudes and strategies are analyzed the light of literature.